Leaders development program by 360 degree feedback: reflection on head nurses' leadership practices - Sabrine Mohammed Emam; Samah Faisal Fakhry; Hanaa Mohamed Abdrabou (BMC, 2024)
Abstract Background Leadership in nursing is crucial for delivering high-quality healthcare and ensuring positive outcomes for patients, staff, and institutions. Many nurses in leadership positions lack formal training, which can compromise their effectiveness. This study aims to evaluate the effect of a leadership development program utilizing 360-degree feedback on head nurses' leadership practices. Methods A true-experimental design was employed in three healthcare institutions. The study involved 80 head nurses (40 intervention, 40 control), 240 staff nurses, and 29 supervisors. The intervention group participated in a six-week leadership development program using 360-degree feedback. Data were collected pre- and post-intervention using the Leadership Development and 360-Degree Feedback Knowledge Questionnaire and the Leadership Practices Inventory (LPI). Results The intervention group showed significant improvements in leadership knowledge and practices across all dimensions. Knowledge scores increased from 25.1 ± 8.8 to 93.0 ± 5.1 post-intervention, maintaining at 83.2 ± 7.1 at follow-up. Self-assessed leadership scores improved from 88.1 ± 6.0 to 97.5 ± 2.7, and 98.5 ± 2.0 at follow-up. Supervisor and staff assessments also showed substantial increases. Multiple linear regression analyses confirmed the strong positive impact of the intervention on leadership outcomes. Conclusion The leadership development program using 360-degree feedback significantly enhanced head nurses' leadership knowledge and practices. The results suggest that such programs can improve leadership capabilities in healthcare settings, leading to better patient care and organizational performance. Future research should address group homogeneity and explore long-term impacts on patient outcomes.